2010
DOI: 10.1007/s11684-010-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications of astrocytes in neurovascular coupling

Abstract: Normal brain function requires continuous supply of oxygen and glucose in a strict manner. The close spatial and temporal relationship between neural activity and cerebral blood flow (CBF) is termed as neurovascular coupling, which is dependent or not dependent on astrocytes. The increase in flow evoked by brain activity is mediated by the concerted action of multiple mediators that originate from different cells and act at different levels of the cerebral vasculature. More studies are needed for further under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous research in TBI including ours has found that oxidative stress and mitochondrial dysfunction play a major role in ischemia induced neuronal damage 2 , 7 , 8 . The brain functions exclusively under strict aerobic conditions and as such, it is subject to the by-products of aerobic respiration specifically reactive oxygen species (ROS) 9 . ROS at high concentrations can induce degradation of cellular structures leading to impaired cellular function and cell death 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in TBI including ours has found that oxidative stress and mitochondrial dysfunction play a major role in ischemia induced neuronal damage 2 , 7 , 8 . The brain functions exclusively under strict aerobic conditions and as such, it is subject to the by-products of aerobic respiration specifically reactive oxygen species (ROS) 9 . ROS at high concentrations can induce degradation of cellular structures leading to impaired cellular function and cell death 10 .…”
Section: Introductionmentioning
confidence: 99%